Patient with depression poisoned with psychopharmaceutics and ethanol – case report - Janeczko, Dominika Anna; Orzeł, Anna; Klatka, Barbara; Hołowczuk, Magdalena; Terpiłowski, Michał; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
In Poland in 2016, there were almost 10,000 suicide attempts, in which about 55% ended up with death. Suicidal attempts are more often taken by women, but they are more effective in the case of men. Most of these people are afflicted with mental illness such as depression. A 49 year old man was admitted to Cardiology and Toxicology Department, because of poisoning with antipsychotic drugs and ethanol. It was his second suicide attempt. The day he was admitted to the hospital he was in serious condition. Patient was monitored, symptomatic treatment and pharmacotherapy were initiated. The patient required intubation and the use of respiratory therapy because of breathing problems. In the clinical study and imaging examinations massive pneumonia, was confirmed. His pharmacotherapy was modified and the antibiotics were given because of inflammation of a lungs. For patients poisoned by various substances, respiratory failure often has a complex medium. It may result from the depression itself of the xenobiotics on the respiratory system, the influence of the indirect mechanism of breathing or the result of aspiration and development of pneumonia. In therapy the most important is the monitoring of the patient’s condition, electrolyte imbalance and symptomatic treatment. In a few cases and only for some drugs, we can use a specific antidote.